Mais que avós: os bisavós na perspectiva das diferentes gerações - Schuler, Emily (2018)
The increase of human aging is a phenomenon observed in world scale and allows the experience of several roles within the family. Nowadays grandparents can see their grandchildren growing up and having children, become great-grandparents, and thus add another generation in the network of relationships. Consequently, more and more multigenerational families are emerging, formed by four or even five generations, and therefore more vertically. Thus, the objective of this research was to understand the role of great-grandparents, as well as the intergenerational repercussions of this role in their lives and that of their relatives. More specifically it was intended: to analyze the meaning of being great-grandparents in the family, from the perspective of each generation; identify the activities performed by their great-grandparents; identify the legacy that the great-grandparents wish to convey; characterize the needs and feelings experienced by the great-grandparents and their families; understand intergenerational relations permeated by the presence of great-grandparents among family members. It is a multiple case study with four families consisting of four generations and one family with five generations, thus totaling twenty-two participants. Three great-grandmothers, two great-grandfathers, and a great-great-grandmother. As for the other generations, five children, grandchildren, great-grandchildren and a great-great-grandmother were interviewed. As a research instrument, a semi-directed interview was used, with a specific script for each generation, as well as a questionnaire with the sociodemographic data of the participants. The data were analyzed through thematic content analysis. The main results pointed out the following: 1) As for the feelings experienced when becoming great-grandparents, they reported joy, satisfaction and gratitude; 2) The support provided by them, most of the time, is of the emotional type; 3) The family relationship appeared as quite significant, being characterized especially in the form of visits; 4) Conflicts exist, but seem to be circumvented with wisdom and much respect; 5) The legacies transmitted by them are related to faith, solidarity, education and order; 6) The meaning of being great-grandmother is intimately linked to the feeling of transcendence, the sense of having fulfilled the purpose of life and also its continuity in grandchildren and great-grandchildren. In other generations, the appreciation of the great-grandparents, perceived as wise people, has been observed and can contribute as teachers to the new generations. It is hoped to give visibility to this generation still little studied in our country.